Influence of Seismic Source Parameters on the Excitation Wavelet in Seismic Explorations Based on Numerical Simulation - Ruohua Qiu; Zhaoxing Dong; Yanjun Qi; Yanhui Wang; Lidong Xie; Honghua Liu (Advances in Civil Engineering)
Explosives are the most common seismic source in seismic explorations, whose excitation effect is closely associated with their properties, weight, buried depth, and charging constitution. This study analyzes the influence of seismic source parameters on the features of the explosion wavelet. The explosion process of the seismic source in marine carbonate is numerically simulated with the finite element software LS-DYNA. We consider three parameters, including buried depth, charge weight, and decoupling coefficient. To verify the simulation outcomes, we also carry out field observations. The appropriate buried depth of the explosive should be determined according to stratum lithology. As the charge weight increases, low-frequency energy of the source wavelet increases rapidly. The optimum charge weight is 16–18 kg, and the ideal charging structure is in a concentrated, short-column shape. Compared with the buried depth and charge weight, the decoupling coefficient shows more noticeable influence on the excitation effect of the source wavelet, and the optimum coefficient lies between 2.5 and 3. The results of this study may provide reference data for designing explosion parameters in field seismic explorations.